A view on medical care globalization and medical tourism - Samlee Plianbangchang (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - The purpose of this paper is to disseminate among concerned professionals its certain operational aspects, including some possible implications on health and medical care practices. Design/methodology/approach - It is written on the basis of the author's special study of a diverse source of information, as well as on author's practical experience and observation in this particular area. Findings - Special attention is paid to possible public health impacts within a broad social and economic framework, as well as to its impacts on the existing national health care systems in countries, that would possibly lead to certain degree of inequity in health at national level as an important consequence of health development progress. Originality/value - Knowledge and understanding gained from this paper might be useful in the efforts to develop and manage national health care systems to ensure a reasonable balance in health status of people of all groups.